Electron microscope study of a case of Australia antigen-positive chronic hepatitis. Issue 2 (February 1973) - Almeida, June D.; Gioannini, P.; Scalise, G.; Harrison, C. V.
Abstract : The laboratory findings in a case of Australia antigen (Au-Ag) positive chronic hepatitis in a 4-year-old boy are given. Studies by the electron microscope technique of thin sectioning revealed the presence of 200Å particles in the nuclei of hepatocytes. These particles are identical to those described previously in occasional specimens of Au-Ag-positive liver tissue. However, the pattern found here differs from previous descriptions inasmuch as no heavily infected nuclei could be found but almost all nuclei could be shown to contain extremely small numbers of these particles. The significance of this finding is discussed and the danger that it would be easy to obtain false negatives in similar tissue pointed out.